Analysis of Media Agenda Setting During and After Hurricane Katrina: Implications for Emergency Preparedness, Disaster Response, and Disaster Policy - Barnes, Michael D. (American Public Health Association, 2008)
Media agenda setting refers to the deliberate coverage of topics or events with the goal of influencing public opinion and public policy. We conducted a quantitative content analysis of 4 prominent newspapers to examine how the media gathered and distributed news to shape public policy priorities during Hurricane Katrina. The media framed most Hurricane Katrina stories by emphasizing government response and less often addressing individuals’ and communities’ level of preparedness or responsibility. Hence, more articles covered response and recovery than mitigation and preparation. The newspapers studied focused significantly more on government response than on key public health roles in disaster management. We discuss specific implications for public health professionals, policymakers, and mass media so that, in the future, coordination can be enhanced among these entities before, during, and after disasters occur.